EPISTIMOLOGI PENDIDIKAN ISLAM MENUJU PERSPEKTIF GENDER - Badriyah, Laila (Jurnal al Hikmah, 2017)
Education is one of the strategic means of transforming the culture that developed in the community. The discourse on gender is an interesting thing, both historically and todays modern realities. Islamic education epistimologi give space to women as "equal partners" with men, as al-quran position the rights and obligations of both the anatomy different. Islam emphasizes the concept of justice for anyone and to anyone regardless of their sex.